165k views
17 votes
5^(9x)=25^(4x+2) SHOW STEPSSSS

User MarkWalls
by
6.1k points

1 Answer

10 votes

Answer:

x = 4

Explanation:


5^(9x) =25^(4x+2)

First you need to get a common base as your number.


5^(9x) =5^(2(4x+2))

The second number changed because 5 squared is 25. Changing it to this form gives us the same base number of 5. Now we use the distributive property in the exponent.


5^(9x) =5^(8x+4)

Now we can use this statement:


A^(m) =A^(n) if
m=n

Using this we solve:

9x = 8x+4

-8x -8x

x = 4

Hope it helps!

User James Whiteley
by
6.2k points